The ethnographic study of the student experience of making meaning and identity through a new Veterinary curriculum - Mann, Claire (2013)
In 2007 the first brand new Vet School built in over fifty years in the UK, opened at the University of Nottingham. Innovative evidence-based approaches were taken to each aspect of the new Vet School from the ICT infrastructure, staff recruitment through to curriculum design. This is a relatively rare scenario which offers a unique opportunity for research into this set of innovations and their cumulative effect on the student experience. Research into the student experience is timely and relevant. The world knowledge base is rapidly expanding, in part due to digitality, especially in relation to medical and professional learning. This, with the accompanying disappearance of the 'job for life', has led to increased emphasis within education to develop transferable skills and lifelong learning. As the Higher Education (HE) market becomes more competitive, the student role in the market develops towards consumerism. These factors give impetus for studies into new and developing student learning experiences. The author is an educationalist with no veterinary expertise. Due to this outsider perspective, an emergent ethnographic approach was taken to the research. Data sources are wide ranging from participation observation and field notes to recurring interviews with ten key informant students. Analysis was undertaken through thematising data and iterative ethnographic writing, simultaneously with literature review. Data is presented firstly in a series of descriptive vignettes which highlight key findings. Further to this, analysis is presented and underpinned by examples from primary and secondary data. Key issues are described from a majority rule position but also highlighting negative cases. This approach is useful to represent experiences of a community from a combination of participant perspectives. The research is undertaken in the socio-cultural paradigm where learning is not an individual pursuit but one undertaken in a social context. Wenger's (1999) 'Communities of practice' model describes learning as activity through participation in a community during which individuals construct meaning and identity. This model is most often reported in the literature in relation to informal work-based learning as it is argued that distance between context and classroom creates an artificial learning environment. This thesis takes a novel approach to apply the "Communities of Practice" model to a formal learning environment and considers Higher Education to operate at the 'legitimate periphery of participation' of workplace professionalism. By using Wenger's model as a broad framework, the research highlights the importance of both curriculum and relationships to the student learning experience. Evidence-based educational approaches such as integrated curriculum and early reflective learning were shown to be beneficial to student learning, although the student understanding of the benefits of these approaches on their learning developed longitudinally across the early part of the course. Students participate in learning through the important relationships which exist between peers, students and teachers, and those within the experienced veterinary community of practice. Data showed that talk in both formal and informal relationships is a method used by students in constructing conceptual meaning, and is one way that learners understand their construction of a professional identity during the early part of the course. Cognitive, social and experiential congruence between students and others is shown to have impact on the student learning experience. Specific case examples show that the student experience of a wide range of relationships covering each type of congruence has maximum benefit. Peer learning has significant benefits, and talk and discussion are key to developing both meaning and identity. Professional identity is constructed during both formal and informal, planned and emergent contexts. Significant others act as role models or anti-role models in the student learning journey. SVMS learners develop a professional learning identity related to the nature of knowledge and lifelong learning. A brief summary of the most recent British Veterinary Association (BVA) and Association of Veterinary Students (AVS) student satisfaction survey (2008) concludes that Nottingham has the highest levels of satisfaction and perceived readiness for practice amongst its students of any UK Vet School. This research shows the way that students in the new Vet School learn to both 'talk the walk' and 'walk the walk'.